Genetic Structure of Metaphrynella sundana in Sarawak - Wan Nur Fatanah, Wan Mohammad (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Information of genetic structure of Metaphrynella sundana (Anura: Microhylidae) in Sarawak is lacking. Cytochrome b (cyt b) was used to infer this study in Batang Ai, Matang and Jagoi populations. A total of 582 bp from 800 bp of cyt b gene from six samples were extracted using Cetyl trimethylammonium bromide (CTAB) protocol and it was being amplified using Polymerase Chain Reaction (PCR) approach. Genetic structuring of M. sundana within all populations determined based on haplotype structure. No major clades of western and eastern part of Sarawak was observed with no sharing of haplotype between populations, hence suggesting M. sundana as a more recent lineage. High migration events (Nm) and low population subdivision (Fsc) values indicated that the genetic between populations are homogenous in spite of historical association among western and eastern population of M. sundana in Sarawak, thus suggesting that this species dispersed throughout Sarawak. Population of M. sundana was also said undergone panmixia and the population is still expanding which supported by P-values of Fu's Fs test of neutrality.